A Case Report: Clozapine in Diabetic Patient with Bipolar Mood Disorder - _ Vera; Christine Sitha (Universitas Kristen Maranatha, 2015)
Depression and diabetes are often occur together and their morbidity has a significant impact of health outcomes. Antidepressants dan antipsychotics may cause metabolic abnormalities, as well as neurologic abnormalities. 52 years old diabetic woman presented to Immanuel Teaching Hospital with slurred speech. Since ten years ago, she had bipolar mood disorder, which was recently treated with clozapine. As patient consumed higher dose of clozapine (beyond her psychiatrist’s supervision), she had uncontrolled blood glucose level, fever, and slurred speech. The side effects of clozapine (weight gain, increased insulin resistance, dysarthria, fever) were discussed in this case report. During hospitalization, with strict supervision of clozapine use, the symptoms resolved. In diabetic patients with comorbid psychiatric disorders, a good collaboration between internist and psychiatrist is required to manage the patients effectively and comprehensively. Keywords: bipolar mood disorder, clozapine, diabetes mellitus, depression